Investigation of nonlinear wave-ice interaction using parameter study and numerical simulation - Hartmann, Moritz Cornelius Nikolaus; Bock und Polach, Rüdiger Ulrich Franz von; Ehlers, Sören; Hoffmann, Norbert; Onorato, Miguel; Klein, Marco (ASME, 2020)
This paper investigates the question of the existence of nonlinear wave-ice interaction with the focus on nonlinear wave propagation and dispersion of waves. The scope of this investigation is to provide a better understanding of ice and wave conditions required to observe nonlinear wave effects under level ice. Direct numerical simulations of nonlinear waves in solid ice are performed within the weakly nonlinear Schrödinger equation (NLSE) framework, using the theoretical findings from Liu and Mollo-Christensen’s 1988 paper. Systematic variations of wave and ice parameters address the impact of the mechanical ice properties and ice thickness on traveling waves of certain wave lengths. The impacts of parameter characteristics on nonlinear focusing and wave dynamics, as well as possible constraints regarding physical consistency, are discussed. It is presented that nonlinear focusing in level ice occurs theoretically. Hereby, distinctive areas of validity with respect to nonlinear wave focusing are identified within the parameter study, which strongly depends on the material properties of the level ice. The results obtained in the parameter study are subsequently used to investigate wave focusing under level ice. Therefore, an exact solution of the NLSE, the Peregrine breather, is utilized. The analytical solution for level ice is compared to the open water solution and accompanied by direct numerical simulations. These investigations show that nonlinear wave focusing can be predicted under level ice for certain parameters. In addition, the agreement of the direct simulations and the analytic solution verifies the numerical approach for nonlinear waves in solid ice.